Parallel Development? Productivity Growth Following Electrification and the ICT Revolution - Harald Edquist (Research Institute of Industrial Economics (IFN), 2007)
This paper investigates labor productivity growth and the contribution to labor productivity growth in Swedish manufacturing during electrification and the ICT revolution. The paper distinguishes between technology-producing, intensive and less intensive technology-using industries during these technological breakthroughs. The results show that labor productivity growth and the overall contribution to labor productivity growth was considerably higher in technology-producing industries following the ICT revolution. Moreover, the results presented here show no evidence that industries that were early adopters of electric motors and ICT, on average would have contributed more to productivity growth in Swedish manufacturing.
Keywords: N64; O33; O47; 330; Electrification; ICT Revolution; Productivity Growth; Technological Change; Produktivität; Wirtschaftswachstum; Technischer Fortschritt; Elektrizitätspolitik; Informationstechnik; Wirtschaftsgeschichte; Schweden